2008
DOI: 10.1111/j.1365-2044.2008.05636.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pneumoperitoneum and Trendelenburg position on acute cerebral blood flow–carbon dioxide reactivity under sevoflurane anaesthesia

Abstract: SummaryThis study compared cerebral blood flow–carbon dioxide (CBF–CO2) reactivities in the supine and modest Trendelenburg position under pnemoperitoneum during sevoflurane anaesthesia. After induction of anaesthesia in 25 patients, mechanical ventilation was adjusted to increase Paco2 from 4.7 (T1) to 6.0 kPa (T2) in the supine position, and the change in jugular bulb oxygen saturation was measured as an index of CBF. Then, after establishment of pneumoperitoneum and 30° Trendelenburg position, the CO2 step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…12,28 The CVR-CO 2 reactivity did not change when clonidine was added to propofol. 28 When added to sevoflurane, the CVR-CO 2 was attenuated in the hypercapnic range, but maintained in the hypocapnic range. 12 Addition of ketamine to propofol does not affect the CVR-CO 2 .…”
Section: Effect Of Other Anesthetic Agents On Cvr-comentioning
confidence: 97%
See 1 more Smart Citation
“…12,28 The CVR-CO 2 reactivity did not change when clonidine was added to propofol. 28 When added to sevoflurane, the CVR-CO 2 was attenuated in the hypercapnic range, but maintained in the hypocapnic range. 12 Addition of ketamine to propofol does not affect the CVR-CO 2 .…”
Section: Effect Of Other Anesthetic Agents On Cvr-comentioning
confidence: 97%
“…Studies have shown that both inhalational agents [5][6][7][8][9][10][11][12][13][14][15][16] and intravenous agents [17][18][19][20][21][22][23][24] have variable effects on CVR-CO 2 . This effect is further modified by many physiological factors (age, body position) [25][26][27][28][29] and other medical comorbidities (diabetes, hypertension, stroke, intracranial pathologies). 9,30-41 Adding nitrous oxide (N 2 O) with anesthetic agents further alters the CVR-CO 2 and exact mechanism for this effect is not clear.…”
mentioning
confidence: 99%
“…These findings are consistent with the results of this study. The maintenance of rSO 2 could in part be explained by the fact that arterial carbon dioxide tension increased (from 4.67 (0.59) kPa to 5.73 (0.59) kPa in this study) and this improved cerebral blood flow and compensated for declines in CPP [10]. Theoretically, if an increment of mean arterial pressure associated with the Trendelenburg position during carbon dioxide pneumoperitoneum [11] exceeds increments of central venous pressure or intracranial pressure, CPP would increase significantly after adopting the Trendelenburg position during pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 60%
“…IOP was found to be increased by an average of 13 mmHg after being positioned in the 25 o Trendelenburg position with 15 mmHg of CO 2 pneumoperitoneum, compared with the preinduction value, with surgical duration and ETCO 2 being significant predictors [39]. Cerebral blood flow-carbon dioxide reactivity does not change under the steep Trendelenburg position with pneumoperitoneum during sevoflurane anesthesia [40], and cerebral oxygen saturation, measured with near-infrared spectroscopy, was increased slightly during surgery, mainly related with PaCO 2 [41]. Jugular venous oxygen saturation does not seem to reflect brain oxygenation better than rSO 2 in this condition [42].…”
Section: Prostatectomymentioning
confidence: 89%